Phosphate fertilization with organomineral fertilizer on corn crops on a Rhodic Khandiudox with a high phosphorus content - Grohskopf, Marco Andre [UNESP]; Correa, Juliano Corulli; Fernandes, Dirceu Maximino [UNESP]; Benites, Vinicius de Melo; Teixeira, Paulo Cesar; Cruz, Caio Vilela [UNESP] (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to evaluate the nutritional content and grain yield of three corn (Zea mays) crops in response to phosphate fertilization with an organomineral fertilizer based on poultry litter or a mineral fertilizer, when cultivated on a Rhodic Khandiudox with a high initial phosphorus content. The experiment was carried out in the field in a randomized complete block design in a 2x4+1 factorial arrangement (organomineral or mineral fertilizer x 20, 40, 60, or 80 kg ha(-1) P + control treatment with no phosphate fertilization), with four replicates each. Available P and total organic carbon (TOC) contents in the soil at the end of the crop cycle, plant tissue P contents, and grain yield were determined. The agronomic efficiency index (AEI) was estimated based on corn grain yield. After three harvests, soil available P and TOC contents did not increase significantly due to fertilizer use, but were directly related to P doses. In a Rhodic Khandiudox with a high initial P content, the use of an organomineral fertilizer based on poultry litter promotes higher corn crop yield, with an AEI 20% higher than that of the mineral fertilizer.
Keywords: agronomic efficiency; fertilization; mineral fertilizer; organic waste